Ice slurry ingestion as a cooling strategy in the heat - Jumpei Osakabe; Takaaki Matsumoto; Yoshihisa Umemura (Japanese Society of Physical Fitness and Sports Medicine, 2019)
It is well known that excessively elevated core body temperature owing to prolonged exercise in high temperatures causes heat-related illness and has a negative impact on exercise performance. Many articles have been published about effective cooling methods to avoid such impacts on physiological functions in the heat. Ice slurry ingestion has been used by many athletes as a practical and effective cooling strategy. Ice slurry can easily be used on sports fields. Moreover, ice slurry reduces core body temperature more effectively than water alone. Thus, ingestion of ice slurry may be one of the best cooling strategies in hot temperatures. This article provides an overview of the effects of ice slurry ingestion on core body temperature, thermal perception, and exercise performance, and offers practical recommendations in the field that can be adopted by athletes and coaches.